Are small and medium enterprises (SMEs) planning for strategic marketing in South Africa? - Louise van Scheers; Khathutshelo Mercy Makhitha (Foundations of Management, 2016)
Substantial evidence shows that strategic marketing planning leads to increased small business performance, yet most small business owners do not draw up a plan for their businesses. This paper presents the results of a secondary research survey on strategic marketing planning of SMEs in South Africa. They indicate that while the higher performing SMEs give a higher priority to marketing than to other business functions, they are still sales- or production-oriented. The higher performing SMEs are more aware of strategic planning tools. They compete with value-added products and good buyer-seller relationships. The findings suggest that broad, small business marketing principles to some extent contribute to the success of SMEs.
Keywords: 650; strategic marketing planning; South African SMEs; better performing SMEs; lack of strategic planning know-how